Biological and molecular characterization of Rachiplusia nu single nucleopolyhedrovirus, a promising biocontrol agent against the South American soybean pest Rachiplusia nu - Jakubowicz, Violeta (2019)
Rachiplusia nu (Lepidoptera: Noctuidae) is a key soybean pest in Argentina. Current management of this moth relies mainly on the use of synthetic insecticides and transgenic plants. In search of biological control-based alternatives, a baculovirus from R. nu (hereafter RanuNPV) was characterized and its insecticidal properties tested under laboratory conditions. RanuNPV occlusion bodies (OBs) were nearly tetrahedral, averaging 1.0 ± 0.2 μm in their longest edge and containing singly enveloped nucleocapsids. Histopathology of infected late-instar larvae revealed broad tissue tropism, where fat bodies and epidermis were the most affected organs. Phylogenetic analysis of concatenated polh, lef-8 and lef-9 partial sequences classified RanuNPV as a new species that clusters with other group II alphabaculoviruses infecting larvae of Plusiinae. Bioassays performed with R. nu neonates determined the median lethal dosage to be approximately 2.5 OBs/larva; most insects died within 4–5 days post inoculation showing typical baculovirus-induced liquefaction. No effects were observed in other lepidopteran species assayed, including Spodoptera frugiperda, Cydia pomonella and Diatraea saccharalis. High pathogenicity and host specificity make RanuNPV a good candidate for controlling R. nu.